DOES EVERYTHING ENDS IN THE DRAWINGS!? - NOTES ON A RESEARCH WITH CHILDREN'S - Batista Ferreira, Edith Maria [UNESP] (Fundacao Univ Tocantins, 2023)
The graphism is one of the oldest languages of humanity. Despite this, it is a field that presents itself as fertile, due to the lack of production, especially when it comes to children's drawing. This article aims to share the reflections made on drawing as language, documentary source and cultural artifact, from the concerns felt in the relationship with children in a virtual educational space. This is a qualitative research and for its realization, participant observation was used in a class of Infantil II, in a remote context, during the first semester of 2021, Period of social distancing as a result of the Covid-19 pandemic. The results pointed out the drawing as language and a human product, manufactured by the child, woven into a web of meanings that brings information about the culture of its creator, settled in time and space. Documents and keeps memories, knowledge about various social and cultural contexts, evidencing a singular look at the world.
Keywords: Children's Drawing; Language; Cultural Artifact; Documentary Source